An Exploratory Investigation of the Role of Openness in Relationship Quality among Emerging Adult Chinese Couples - Zhou, Yixin; Wang, Kexin; Chen, Shuang; Zhang, Jianxin; Zhou, Mingjie (Frontiers in Psychology, 2017)
This study tested emerging adult couples’ openness and its fit effect on their romantic relationship quality using quadratic polynomial regression and response surface analysis. Participants were 260 emerging adult dyads. Both dyads’ openness and relationship quality were measured. The result showed that (1) female and male openness contribute differently to relationship quality; (2) couples with similar high openness could experience better relationship quality than those with similar low openness traits; and (3) when dyadic openness is dissimilar, it is better to be either relatively high or relatively low than to be moderate. These findings highlight the role of openness in emerging adults’ romantic relationships from a dyadic angle.